Pregnancy in MuSK‐positive myasthenia gravis: A single‐center case series - Harada, Yohei; Bettin, Margaret; Juel, Vern C.; Hobson‐Webb, Lisa D.; Raja, Shruti M.; Sanders, Donald B.; Massey, Janice M. (Muscle & nerve, 2023)
Introduction/Aims Myasthenia gravis (MG) with muscle‐specific tyrosine kinase (MuSK) antibodies (MMG) is predominantly seen in women of childbearing age. Our objective in this study was to describe the course of MMG during pregnancy and within 6 months postpartum, and to document any effect on fetal health. Methods A retrospective review was performed of medical records of patients with MMG seen in the Duke Myasthenia Gravis Clinic from 2003 to 2022. MMG patients with onset of MMG symptoms before or during pregnancy as well as within 6 months postpartum were reviewed. Results A total of 14 pregnancies in 10 patients were included in our study cohort. Initial MG symptoms developed during pregnancy or within 6 months postpartum in six patients. Four patients had two pregnancies, three of whom developed MG during their first pregnancy. In the patients diagnosed before pregnancy, MG symptoms increased in five of eight patients during pregnancy or postpartum. Four patients required rescue therapy with plasma exchange or intravenous immunoglobulin during pregnancy or postpartum. One patient had a cesarean section after prolonged labor due to failure of progression. There were no other complications of pregnancy or delivery, and all infants were healthy at delivery. Discussion As in non‐MuSK MG, women with MMG may also have worsening or may develop initial MG symptoms during pregnancy or within 6 months postpartum. More aggressive medical therapy may be required for pregnant patients with MMG. Further study is needed to identify the mechanism and risk of worsening of MMG during pregnancy or postpartum.